Radiological evaluation of a calyceal diverticulum presenting with hematuria - Federica Masino; Manuela Montatore; Laura Eusebi; Rossella Gifuni; Gianmichele Muscatella; Marina Balbino; Giuseppe Sortino; Lucia Pitoni; Giuseppe Guglielmi (Digital Diagnostics)
Calyceal diverticula, also known as pyelogenic cysts, are a relatively uncommon condition, which is usually asymptomatic and incidentally diagnosed during routine imaging. In some cases, they may lead to concerning symptoms such as hematuria and flank pain, mimicking a renal tumor. In this case report, the patient suffered from hematuria that was initially suspected as a renal malignancy but was ultimately attributed to a calyceal diverticulum. The presented case allows evaluating one of the rarest and underestimated causes of hematuria and describes the main imaging features of calyceal diverticula. In particular, ultrasonography, computed tomography urography, dual-energy computed tomography, and magnetic resonance urography were performed. Subsequently, this case report also serves an educational purpose.